2013
DOI: 10.1371/journal.pone.0069123
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Analysis of the Peripheral and CNS Effects of Systemic LPS, IL-1Β, TNF-α and IL-6 Challenges in C57BL/6 Mice

Abstract: It is increasingly clear that systemic inflammation has both adaptive and deleterious effects on the brain. However, detailed comparisons of brain effects of systemic challenges with different pro-inflammatory cytokines are lacking. In the present study, we challenged female C57BL/6 mice intraperitoneally with LPS (100 µg/kg), IL-1β (15 or 50 µg/kg), TNF-α (50 or 250 µg/kg) or IL-6 (50 or 125 µg/kg). We investigated effects on core body temperature, open field activity and plasma levels of inflammatory markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
182
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(210 citation statements)
references
References 129 publications
16
182
1
Order By: Relevance
“…Quantitative PCR was performed on a CFX96 touch real-time PCR detection system (Bio-Rad) using the SsoFast probes supermix (BioRad) according to the manufacturer's recommendations. Quantitative PCR was performed using a primer/probe set designed to amplify PTX3 (forward, 5=-ACAACGAAATAGACAATGGACTTCAT-3=; reverse, 5=-C TGGCGGCAGTCGCA-3= probe, 5=-CCACCGAGGACCCCACGCC-3=; Sigma-Genosys) as previously described (37) and an 18S rRNA endogenous control (Life Technologies). Expression of PTX3 mRNA from S. aureus-infected wounds was compared to that of wounds from control mice treated with PBS by the change-in-cycle-threshold (⌬⌬C T ) method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative PCR was performed on a CFX96 touch real-time PCR detection system (Bio-Rad) using the SsoFast probes supermix (BioRad) according to the manufacturer's recommendations. Quantitative PCR was performed using a primer/probe set designed to amplify PTX3 (forward, 5=-ACAACGAAATAGACAATGGACTTCAT-3=; reverse, 5=-C TGGCGGCAGTCGCA-3= probe, 5=-CCACCGAGGACCCCACGCC-3=; Sigma-Genosys) as previously described (37) and an 18S rRNA endogenous control (Life Technologies). Expression of PTX3 mRNA from S. aureus-infected wounds was compared to that of wounds from control mice treated with PBS by the change-in-cycle-threshold (⌬⌬C T ) method.…”
Section: Methodsmentioning
confidence: 99%
“…To further establish the differential in vivo effects on IL-1␤ signaling induced by these individual strains, we measured gene expression of pentraxin-related protein (PTX3) at the wound infection site. Expression of PTX3 has been shown to be induced during S. aureus infection (24), and importantly it appears that IL-1␤ is specifically responsible for its induction (37,40). Consequently, PTX3 has the potential to be used as a surrogate marker for assessment of IL-1␤ protein synthesis and bioactivitiy in vivo (37).…”
Section: And Cd3mentioning
confidence: 99%
“…It is worth noting that in the stressful condition, microglial IL-6 expression is affected by treatment in an opposite fashion as compared to the expression of other pro-inflammatoryrelated genes. Previous studies have already found unique IL-6 expression profile compared to that of other pro-inflammatory cytokines in response to stressful (Audet et al, 2010) or immunogenic stimuli (Skelly et al, 2013). In addition, IL-6 has been reported to produce unexpected effects when used to modulate a variety of physiological processes, such as memory function (Arnold et al, 2002;Yirmiya and Goshen, 2011).…”
Section: Microglial Modulation By Fluoxetine Upon Environmental Stimumentioning
confidence: 99%
“…However, it is unclear if this lack of correlation between inflammatory markers was reflected centrally. Previous research has shown that relationship between TNF and other cytokines differ in the periphery and the CNS (Skelly et al, 2013). In addition, we restricted our analysis to those cytokines that have shown significant elevation in depressive illnesses.…”
Section: I]mentioning
confidence: 99%